3D Diorama Learning Media on the History of the Independence of Indonesia to Improve Learning Outcomes in Social Studies Learning - Hanifah, Chansa Salwa; Setyasto, Novi (MIMBAR PGSD Undiksha, 2024)
Social studies learning still needs to be more optimal. This problem is motivated by the need for more relevant learning media. This results in students tending to be passive and affecting learning outcomes, which are still low. This research aims to develop 3-dimensional diorama media for social studies lesson content in elementary school classes. This type of research is in the form of research and development, the Borg and Gall development model. Data collection techniques include tests and non-tests in the form of observations, interviews, tests, questionnaires, and documentation. The data collection instruments are in the form of questionnaires and test questions. Data analysis techniques use product data analysis, Kolmogorov-Smirnov normality test data analysis, paired t-test, and N-Gain test. The research results show that 3-dimensional diorama media is suitable for use with a percentage of media expert assessment of 81.25% and material experts of 94.4%. The t-test results show that the media used is effective in learning to improve social studies learning outcomes on the content of National Events Around the Proclamation of Independence. The N-Gain test results show an increase in social studies learning outcomes. It was concluded that 3-dimensional diorama media was effective and suitable for social studies learning. The research implication is that 3-dimensional diorama media can be used to improve social studies learning outcomes for students.